2012
DOI: 10.4049/jimmunol.1103811
|View full text |Cite
|
Sign up to set email alerts
|

Polyinosinic-Polycytidylic Acid Limits Tumor Outgrowth in a Mouse Model of Metastatic Lung Cancer

Abstract: Polyinosinic-polycytidylic acid (poly I:C), a TLR3 ligand, is currently being tested in human clinical trials as an adjuvant to anti-cancer vaccines and in combination with other therapies. However, little is known about its activity in established pulmonary metastasis. The aim of our study was to elucidate the effect of poly I:C (1, 10, or 100 μg/mouse) in a mouse model of B16-F10–induced metastatic lung cancer. Lung tumor growth was arrested after a single administration of poly I:C. This was associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 25 publications
(37 reference statements)
1
60
0
Order By: Relevance
“…13 Poly(I:C) has been shown to rapidly induce secretion of inflammatory cytokines and to elicit cytotoxic T-cell responses, resulting in strong anti-tumor effects in pre-clinical models. [14][15][16] As Poly(I:C) has limiting toxicity, several modified versions such as PolyI:PolyC12U 17 and Poly(IC:LC) 18 have been developed to reduce toxicity. Currently, several clinical trials are evaluating the adjuvanticity of Poly(IC:LC) in cancer immunotherapy including recurrent pediatric low grade gliomas and stage IV melanoma (listed at http://clinicaltrials.gov/).…”
mentioning
confidence: 99%
“…13 Poly(I:C) has been shown to rapidly induce secretion of inflammatory cytokines and to elicit cytotoxic T-cell responses, resulting in strong anti-tumor effects in pre-clinical models. [14][15][16] As Poly(I:C) has limiting toxicity, several modified versions such as PolyI:PolyC12U 17 and Poly(IC:LC) 18 have been developed to reduce toxicity. Currently, several clinical trials are evaluating the adjuvanticity of Poly(IC:LC) in cancer immunotherapy including recurrent pediatric low grade gliomas and stage IV melanoma (listed at http://clinicaltrials.gov/).…”
mentioning
confidence: 99%
“…Using this model, a previous study reported that NK1.1 + cells and IFN-g have a critical role in the protection of lung metastases (30). Previous studies demonstrated that the IFN-g receptor expressed on host cells, but not on melanoma cells, is important for development of lung metastases (43)(44)(45). Hence, lung metastases are prevented by the IFN-g-inducible immune response following NK cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…Protection conferred by tumor vaccine including Poly(I:C) was mediated by primary and memory CD8+ T cells that has been robustly activated by antigen crosspresenting DC [111][112][113][114][115], and by IFN-I-activated NK cells [115]. Moreover, in a mouse model of established pulmonary metastasis, Poly(I:C) elicited a Th1-like, Th17-like, and cytotoxic immune environment following the activation of DCs and the production of IFN type [116]. Those animal models allowed also to show that combining Poly(I:C) with CD40 signaling dramatically increased the efficacy of mouse tumor vaccine [117,118].…”
Section: Integrated View Of the Activities Of Tlr3 Ligand In Cancermentioning
confidence: 99%